KAJIAN BURNOUT DARI STATUS GIZI PEKERJA DEWASA MADYA - Rona Sari Mahaji Putri; Hilda Mazarina Devi (STIKes Maharani Malang, 2022)
Intoduction: Many middle-aged workers experience burnout. Prolonged burnout resulted in negative impact, from the point of view of health and work productivity. The purpose of the study was to determine the relationship between nutritional status and burnout among middle-aged workers at University X in Malang. Method: This is a descriptive correlation study with a cross-sectional design. The population is all middle-aged employees at University X, within a total of 84 people. The sample were 42 staff from University X who are middle-aged adults in Malang, which were taken by accidental sampling technique. The independent variable in this study was nutritional status, while the dependent variable was burnout syndrome. The burnout questionnaire used as study instrument which combined burnout questionnaire and the Body Mass Index observation sheet. Data analysis using Spearmen-rank test with SPSS software version 18. Results :showed as many as 42.9% of middle-aged workers have an ideal body mass index and the rest are overweight; while as many as 45.2% of each worker had a moderate and high level of burnout. Discussion: More over, results showed that there was no relationship between nutritional status (BMI) and burnout syndrome (p-value 0.676). It is recommended for further researchers to examine the Health Belief Model on burnout syndrome analysis among middle-aged workers. Keywords: activity; burnout; middle-aged workers; nutritional status